Development of prediction models for the sensitivity of oral squamous cell carcinomas to preoperative S-1 administration. Issue 8 (August 2020) - Shiiba, Masashi; Yamagami, Hitomi; Sudo, Tadashi; Tomokuni, Yosuke; Kashiwabara, Daisuke; Kirita, Tadaaki; Kusukawa, Jingo; Komiya, Masamichi; Tei, Kanchu; Kitagawa, Yoshimasa; Imai, Yutaka; Kawamata, Hitoshi; et al.
Abstract: S-1 is an anticancer agent that is comprised of tegafur, gimeracil, and oteracil potassium, and is widely used in various carcinomas including oral squamous cell carcinoma (OSCC). Although an established prediction tool is not available, we aimed to develop prediction models for the sensitivity of primary OSCC cases to the preoperative administration of S-1. We performed DNA microarray analysis of 95 cases with OSCC. Using global gene expression data and the clinical data, we developed two different prediction models, namely, model 1 that comprised the complete response (CR) + the partial response (PR) versus stable disease (SD) + progressive disease (PD), and model 2 that comprised responders versus non-responders. Twelve and 18 genes were designated as feature genes (FGs) in models 1 and 2, respectively, and, of these, six genes were common to both models. The sensitivity was 96.3%, the specificity was 91.2%, and the accuracy was 92.6% for model 1, and the sensitivity was 95.6%, the specificity was 85.2%, and the accuracy was 92.6% for model 2. These models were validated using receiver operating characteristic analysis, and the areas under the curves were 0.967 and 0.949 in models 1 and 2, respectively. The data led to the development of models that can reliably predict the sensitivity of patients with OSCC to the preoperative administration of S-1. The mechanism that regulates S-1 sensitivity remains unclear; however, the prediction models developed provide hope that further functional investigations into the FGs will lead to a greater understanding of drug resistance. Abstract : Genetics; Clinical Genetics; Surgery; Pharmacology; Oncology; anti-tumor agent; 5-fluorouracil; oral squamous cell carcinoma; OSCC; prediction model; S-1.